The Effect of Distance between Sheet Pile and Foundation on Bearing Capacity of Foundation - Ozpolat, Aykut; Aksoy, Huseyin Suha (Wiley, 2022)
In this study, the presence of a foundation near the sheet pile wall built on sand soil was simulated in the laboratory, similar to the field conditions. For this purpose, laboratory tests of sheet pile wall (SPW) (defo) and bearing capacity (q(ult)) of the foundation were carried out by applying vertical loads to the steel model foundation. Besides, laboratory tests were represented by the Mohr-Coulomb material model under 3D plane deformation conditions, and numerical analyses were performed. These studies were performed by varying the distance among the SPW, the foundation (L), and the penetration depth of SPW (Hp). The results demonstrated that L had a greater effect on q(ult) and delta max than the H-p. When L was kept constant and H-p was increased, it was seen that q(ult) increased and delta max decreased. Moreover, the raise in L has resulted in an increment in the qult and delta max decreased. In addition, a good agreement between numerical analysis and experimental test was observed.
Keywords: Braced Excavation; Retaining Wall; Observed Performance; Soil; Behavior; Model; Sand